2022
DOI: 10.52547/iem.8.2.139
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Typing of Streptococcus agalactiae- cMLSB Phenotype Isolates by Enterobacterial Repetitive Intergenic Consensus-PCR (ERIC-PCR) in Isfahan, Iran

Abstract: Backgrounds: Group B Streptococcus (GBS) is an important opportunistic bacterial pathogen that could cause serious infections, especially in neonates, adults, and the elderly. In GBS isolates, a macrolide resistance phenotype that confers constitutive resistance to macrolidelincosamide-streptogramin B antibiotics (cMLSB phenotype) has become a global concern. On the other hand, little is known about the genetic relatedness and diversity of GBS isolates isolated from various patients in Iran. Hence, this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…Our study has identified three main clusters with a similarity of >80%, but very few isolates were completely identical. The situation of non-typeable strains (as in the case of our eight isolates that showed no bands following ERIC-PCR) was also described in other similar studies [40,41].…”
Section: Discussionsupporting
confidence: 84%
“…Our study has identified three main clusters with a similarity of >80%, but very few isolates were completely identical. The situation of non-typeable strains (as in the case of our eight isolates that showed no bands following ERIC-PCR) was also described in other similar studies [40,41].…”
Section: Discussionsupporting
confidence: 84%